2008 International Conference on Audio, Language and Image Processing 2008
DOI: 10.1109/icalip.2008.4590236
|View full text |Cite
|
Sign up to set email alerts
|

Musical instrument identification using Principal Component Analysis and Multi-Layered Perceptrons

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
(8 reference statements)
1
12
0
Order By: Relevance
“…Studies performed using MLPs to classify musical instrument sounds have found able to produce a good result [1,15,18]. Deng et al [1] studied the quality of feature selection and the performance of three feature sets which are MFCC, perception-based and MPEG-7 for twenty instruments.…”
Section: Data Classification Using Mlpmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies performed using MLPs to classify musical instrument sounds have found able to produce a good result [1,15,18]. Deng et al [1] studied the quality of feature selection and the performance of three feature sets which are MFCC, perception-based and MPEG-7 for twenty instruments.…”
Section: Data Classification Using Mlpmentioning
confidence: 98%
“…There were assortments of sampling rate used in the previous work instead of 44.1 kHz as well. For example, 16kHz [14], 22kHz [12] and 32kHz [15]. These variety of parameters used in the literature show that there were no standard benchmarking in determining the best parameter for data representation.…”
Section: A Data Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…This classifier has been used in many machine learning tasks, including for musical instrument classification. 57 The MLP implementation used the open-source WEKA toolbox. 58 The processing and classification methodology was the same for both strategies but was performed independently to produce two alternative MFCC-based classification systems, B-1 and B-2 (see Sec.…”
Section: B Multilayer Perceptron Neural Network Classifiermentioning
confidence: 99%
“…The results obtained with hierarchical classification that improves the score almost to 2% compared to the direct classification.RWC Music Database for musical instrument sound is chosen with isolated notes of instruments. Alicja A. Wieczorkowska, Zbigniew W. Ra´s, Xin Zhang, Rory Lewis [10] done hierarchical classification using Hornbostel-sachs classification and by fifteen different articulation method (blown, bowed, bowed vibrato, concussive, hammered, lip vibrated, muted, muted vibrato, percussive, picked, pizzicato, rubbed, scraped and shaken).Hornbostel-Sachs method gives better result than articulation method. Slim Essid, Ga¨El Richard & Bertrand David [12] selected the feature which has the first rank is selected by Linear Discriminant Analysis (LDA).Analysis and comparison of two hierarchical taxonomies natural instrument families and automatically hierarchical clustering using SVM classifiers are done.…”
Section: Introductionmentioning
confidence: 99%